Slipped-strand mispairing in a plastid gene: ıt rpoC2 in grasses (Poaceae) - Michael P. Cummings; King, L. M.; Kellogg, E. A. (Mol Biol EvolMol Biol Evol, 1994)
An exception to the generally conservative nature of plastid gene evolution is the gene coding for the beta" subunit of RNA polymerase, rpoC2. Previous work by others has shown that maize and rice have an insertion in the coding region of rpoC2, relative to spinach and tobacco. To assess the distribution of this extra coding sequence, we surveyed a broad phylogenetic sample comprising 55 species from 17 angiosperm families by using Southern hybridization. The extra coding sequence is restricted to the grasses (Poaceae). DNA sequence analysis of 11 species from all five subfamilies within the grass family demonstrates that the extra sequence in the coding region of rpoC2 is a repetitive array that exhibits more than a twofold increase in nucleotide substitution, as well as a large number of insertion/deletion events, relative to the adjacent flanking sequences. The structure of the array suggests that slipped-strand mispairing causes the repeated motifs and adds to the mechanisms through which the coding sequence of plastid genes are known to evolve. Phylogenetic analyses based on the sequence data from grass species support several relationships previously suggested by morphological work, but they are ambiguous about broad relationships within the family.